2021
DOI: 10.1101/2021.12.20.21268066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persisting Chemosensory Impairments in 366 Healthcare Workers Following COVID-19: An 11-Month Follow-up

Abstract: Background and Objectives: Olfactory and gustatory dysfunctions (OD, GD) are prevalent symptoms following COVID-19 and persist in 6%-44% of individuals in the first months after the infection. As only few reports have described their prognosis more than 6 months later, the main objective of this study was to assess the prevalence of OD and GD 11 months after COVID-19. We also aimed to determine test-retest reliability of subjective chemosensory ratings for the follow-up of chemosensory sensitivity, as this mea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Upon infection, these cells degenerate which disturbs the local environment which, crucially, results in cell death of olfactory receptor neurons and associated olfactory dysfunction (Cooper et al, 2020; Xydakis et al, 2021). The olfactory system demonstrates, however, a very good ability to regenerate (Reden et al, 2006) which might explain why most of SARS-CoV-2 infected individuals regain olfactory abilities within weeks following the acute phase (Bussiere et al, 2021; Bussiere et al, 2022). It is not yet clear why some individuals do not completely regain their olfactory abilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon infection, these cells degenerate which disturbs the local environment which, crucially, results in cell death of olfactory receptor neurons and associated olfactory dysfunction (Cooper et al, 2020; Xydakis et al, 2021). The olfactory system demonstrates, however, a very good ability to regenerate (Reden et al, 2006) which might explain why most of SARS-CoV-2 infected individuals regain olfactory abilities within weeks following the acute phase (Bussiere et al, 2021; Bussiere et al, 2022). It is not yet clear why some individuals do not completely regain their olfactory abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory dysfunction is the most specific symptom of acute COVID-19 (Gerkin et al, 2021; Rudberg et al, 2020) and smell abilities are heavily impacted by COVID-19 (Parma et al, 2020). Olfactory function recovers in many patients after olfactory dysfunction in the acute phase of COVID-19 (Bussiere et al, 2022). However, a non-negligeable proportion of patients exhibits chronic olfactory dysfunction after COVID-19 (McWilliams et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The data are being collected as part of the follow-up research of this cohort and will be published in the future because the presence of these olfactory dysfunctions may be associated with the recovery of sense of smell. 63,64 The absence of formal data regarding previous clinical history and the acute phase of COVID-19 is a potential confounding factor, which was minimized by carefully using an anamnesis form and specialized consultation with neurologists and otolaryngologists. Future studies should continue the monitoring of this population, prioritizing interdisciplinary research in clinical, epidemiologic, and basic science, such as genetics and immunology.…”
Section: Limitationsmentioning
confidence: 99%
“…Although most patients recover the sense of smell within a few weeks, several authors have reported a significant rate of long‐term OD [ 8 , 9 , 10 ]. Only a few authors have investigated the prevalence of OD 1 year after infection with objective methods [ 11 , 12 , 13 ], and there are no studies with 2‐year follow‐up. Long follow‐up is essential to obtain a reliable estimate of the prevalence of persistent OD.…”
Section: Introductionmentioning
confidence: 99%